Viral Myocarditis and Dilated Cardiomyopathy: Etiology and Pathogenesis - A. Huber, Sally (Current Pharmaceutical Design, 2016)
Myocarditis is an inflammation of the myocardium which often follows microbial infections and is a significant cause of sudden unexpected death in the young (<40 years of age) and an underlying cause of dilated cardiomyopathy. Although histologically, the disease is usually associated with infiltration of the myocardium with either eosinophils or leukocytes, use of immunosuppression is controversial outside of giant cell myocarditis and has been found to be of limited value in lymphocytic myocarditis. The relatively limited response might reflect the need for host immunity to control persistent virus infection in the heart which may be the predominant cause of the chronic myocarditis and dilated cardiomyopathy. Treating the persistent virus infection with interferon-beta improved cardiac function in a clinical trial. However, classic immunosuppressive drugs, such as cyclosporine A and cyclophosphamide, are not effective against all types of immunity and experimental myocarditis models have shown that certain immunopathogenic forms of the disease are resistant to these immunosuppressive agents. Understanding the molecular mechanisms underlying the pathogenesis of this disease and the various infectious agents which can cause it will be essential for developing effective therapeutic agents.
Keywords: immunosuppression